2002
DOI: 10.1073/pnas.142294599
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio /GIAO-MP2-calculated structures and 11 B- 13 C NMR chemical shift relationship in hypercoordinate onium-carbonium dications and isoelectronic onium-boronium cations

Abstract: The boronium-carbonium ion continuum was extended to include hypercoordinated onium-carbonium dications and the isoelectronic onium-boronium cation analogs. Structures and 13 [1]In Eq. 1, the ␦ 13 C is the chemical shift of the cationic carbon of the carbenium ion with respect to tetramethylsilane, and the ␦ 11 B is the chemical shift of the corresponding boron atoms with respect to the BF 3 :OEt 2 . The empirical Eq. 1 is in good agreement with most of the available data. Later, G.K.S.P. et al. (3) reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The magnetic shieldings were calculated on optimized geometries by employing gauge-including atomic orbitals (GIAOs) with the MP2/6-31+G* level of theory. Several reports of Rasul et al have demonstrated that the GIAO-MP2 method can give reliable results for 11 B NMR chemical shift calculations. The 11 B NMR chemical shifts were first computed with B 2 H 6 [the calculated absolute shift, i.e., σ(B), is 103.9] as a reference, which is in accordance with previous (GIAO-MP2) calculations .…”
Section: Computational Detailsmentioning
confidence: 99%
“…The magnetic shieldings were calculated on optimized geometries by employing gauge-including atomic orbitals (GIAOs) with the MP2/6-31+G* level of theory. Several reports of Rasul et al have demonstrated that the GIAO-MP2 method can give reliable results for 11 B NMR chemical shift calculations. The 11 B NMR chemical shifts were first computed with B 2 H 6 [the calculated absolute shift, i.e., σ(B), is 103.9] as a reference, which is in accordance with previous (GIAO-MP2) calculations .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Similarly hypervalent boronium cation (BH 6 + ) is isoelectronic with the corresponding carbonium dication (CH 6 2+ ). Previously we have been able to show a good boronium–carbonium NMR chemical shift relationship for the carbonium dications H 4 CX 2+ and boronium cations H 4 BX + (X = NH 3 , PH 3 , H 2 O, H 2 S, CO, N 2 , HF, HCl, CO 2 , and CS 2 ), based on ab initio/GIAO-MP2 calculations. The general correlation equation is shown below (eq ).…”
Section: Introductionmentioning
confidence: 99%
“…As boron and carbon are consecutive first-row elements, onium−boronium cations 1 are isoelectronic with the corresponding onium−carbonium dications 2 (Scheme ). Recently we have been able to show a good boronium−carbonium NMR chemical shift relationship for the carbonium dications H 4 CX 2+ 2 and boronium cations H 4 BX + 1 (X = NH 3 , PH 3 , H 2 O, H 2 S, CO, N 2 , HF, HCl, CO 2 , and CS 2 ), based on ab initio/GIAO-MP2 calculations. The general correlation equation is shown below (equation 1).…”
Section: Introductionmentioning
confidence: 99%